(untitled) (Homoeopathy for All, 2022)
Background: Hahnemann held that all non venereal chronic diseases are Psoric. That includes most diseases of a chronic nature, all skin diseases, most mental illness other than syphilitic ones, allergies, varicose veins, haemorrhoids, most dysfunctional diseases of organs and systems, etc. Chief Psoric remedies he suggests include Sulphur, Natrum mur, Calc carb, Arsenic alb, Lycopodium, Petroleum, Silica, Zinc amongst many others.1